2015
DOI: 10.1063/1.4913674
|View full text |Cite
|
Sign up to set email alerts
|

What parameters can be reliably deduced from the current-voltage characteristics of an organic bulk-heterojunction solar cell?

Abstract: Through the analysis of scales and simplification of the drift-diffusion device model, we have obtained a quantitative description of the mechanisms underlying the current-voltage (j-V) characteristics of organic bulk-heterojunction solar cells. The mechanisms have been resolved into the competition between the photogeneration, recombination, and extraction/injection rates, which determines the bulk charge carrier concentration; and the combined effect of the built-in field and the boundary layers in shaping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…We showed in a previous publication that fitting JV-curves is clearly insufficient to unambiguously determine physical parameters [ 9 ]. Our conclusions are consistent with Set et al demonstrating that parameter extraction from JV-curve fits are arbitrary [ 119 ]. The parameters are correlated – parameter 1 can have the same influence on the JV-curve as parameter 2.…”
Section: Comprehensive Parameter Extraction With Numerical Simulationsupporting
confidence: 93%
“…We showed in a previous publication that fitting JV-curves is clearly insufficient to unambiguously determine physical parameters [ 9 ]. Our conclusions are consistent with Set et al demonstrating that parameter extraction from JV-curve fits are arbitrary [ 119 ]. The parameters are correlated – parameter 1 can have the same influence on the JV-curve as parameter 2.…”
Section: Comprehensive Parameter Extraction With Numerical Simulationsupporting
confidence: 93%
“…Y.T. Set et al derived a set of implicit equations taking into account second order recombination, which yielded JV -curves in good agreement to the results from 1D drift-diffusion (1D DD) simulations 7 . Ibrahim and coworkers provided explicit analytical expressions to describe the JV -curves of bulk heterojunction solar cells in the limit of uniform bimolecular recombination rates 8 .…”
mentioning
confidence: 69%
“…Device modeling efforts focused on simulations of J – V characteristics in solar cells ,, or SCLC-regime diodes , and time-resolved photocurrents , using various modifications of the semiconductor drift-diffusion model adapted for a particular material and device geometry. A comprehensive review of device modeling of organic BHJ solar cells can be found in ref .…”
Section: Charge Carrier Photogenerationmentioning
confidence: 99%